2018
DOI: 10.1369/0022155417751880
|View full text |Cite
|
Sign up to set email alerts
|

Proteoglycans as Immunomodulators of the Innate Immune Response to Lung Infection

Abstract: Proteoglycans (PGs) are complex, multifaceted molecules that participate in diverse interactions vital for physiological and pathological processes. As structural components, they provide a scaffold for cells and structural organization that helps define tissue architecture. Through interactions with water, PGs enable molecular and cellular movement through tissues. Through selective ionic interactions with growth factors, chemokines, cytokines, and proteases, PGs facilitate the ability of these soluble ligand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
42
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 42 publications
(43 citation statements)
references
References 152 publications
(229 reference statements)
1
42
0
Order By: Relevance
“…Versican is essential during development (76,77) and it is now becoming apparent that it is an important component of the tissue inflammation caused by infection and tissue injury (10). Versican accumulates as part of the early inflammatory response in a number of human diseases often associated with the invasion of leukocytes including those in the vascular system (10,40,(78)(79)(80)(81)(82)(83)(84), lung (5,6,60,77,(85)(86)(87)(88)(89), brain and spinal cord (53,(90)(91)(92), intestine (93)(94)(95)(96), heart (97), liver (63), skin (98,99), eye (100, 101), pancreatic islets (102), and many different forms of cancer [reviewed in (103)(104)(105)]. The accumulation of versican in these tissues is usually associated with other ECM components that bind versican, such as hyaluronan (106,107), link protein, TSG-6, IαI, and CD44 (95, 96, 108-111) (Figure 1).…”
Section: Versican: a Component Of The Inflammatory Responsementioning
confidence: 99%
See 1 more Smart Citation
“…Versican is essential during development (76,77) and it is now becoming apparent that it is an important component of the tissue inflammation caused by infection and tissue injury (10). Versican accumulates as part of the early inflammatory response in a number of human diseases often associated with the invasion of leukocytes including those in the vascular system (10,40,(78)(79)(80)(81)(82)(83)(84), lung (5,6,60,77,(85)(86)(87)(88)(89), brain and spinal cord (53,(90)(91)(92), intestine (93)(94)(95)(96), heart (97), liver (63), skin (98,99), eye (100, 101), pancreatic islets (102), and many different forms of cancer [reviewed in (103)(104)(105)]. The accumulation of versican in these tissues is usually associated with other ECM components that bind versican, such as hyaluronan (106,107), link protein, TSG-6, IαI, and CD44 (95, 96, 108-111) (Figure 1).…”
Section: Versican: a Component Of The Inflammatory Responsementioning
confidence: 99%
“…Recent studies have indicated an important role for the ECM in the inflammatory response (4)(5)(6)(7)(8)(9)(10). Leukocytes cross the endothelial barrier and interact with the ECM which influences their adhesion, retention, migration, and activation.…”
mentioning
confidence: 99%
“…[2,[4][5][6]74] Agrin is a 400 kDa HS-PG of basement membranes which interacts with low-density lipoprotein receptor-related protein-4 (LRP4) and α-dystroglycan in chondrogenic signaling networks supporting chondrocyte differentiation and the upregulation of SOX9 and its transcriptional targets, COL2A1 and ACAN [75] ( Figure 5e). The SLRPs regulate tissue organization, cellular proliferation, adhesion, and responses to growth factors and cytokines [77] in inflammation, [16] cell growth, tissue morphogenesis, and innate immunity. LRP4 interacts with WNTs and BMPs [76] to regulate chondrocyte differentiation.…”
Section: The Cartilage Proteoglycansmentioning
confidence: 99%
“…In addition to their structural roles, they are also dynamic, responsive, regulatory elements of the ECM and participate in cell-cell and cell-ECM communication, the regulation of cellular metabolism, cell proliferation, and differentiation-duties that make them essential for normal tissue function and homeostasis [11] (Figure 2). This has led to the realization that PGs/GAGs could potentially be used in a therapeutic mode to promote repair of tissue defects [12][13][14][15][16][17][18] and the reattainment of functional properties in tissues that had undergone degradative changes due to disease. [15,17,[19][20][21][22] Articular cartilage has an inherently low capacity for self-repair and degeneration of cartilage in diseases such as osteoarthritis (OA) are painful debilitating conditions leading to considerable interest in repair biology for the development of therapies to prevent disease progression to end stage OA.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, the ability of heparan sulfate domains to mediate binding of specific proteins is fundamental to the organization of protein–receptor interactions at the cell surface and for the creation of chemotactic gradients of growth factors and chemokines . For example, heparan sulfate facilitates the interaction of growth factors, such as FGF‐2, VEGF and heparin‐binding epidermal‐like growth factor, with their respective receptors . Upon EC injury resynthesis of membrane bound glycosaminoglycans occurs where sulfation patterns, and consequently also growth factor and morphogen binding, are modified to adapt to the altered microenvironment (for review see Rabelink et al ).…”
Section: The Perivascular Extracellular Matrix As a Signaling Platformentioning
confidence: 99%